Combined use of melatonin and terazosin restores bladder contractility in rabbits with partial outlet obstruction - Onur, Rahmi; Tasdemir, Cemal; Seckin, Dilara; Ilhan, Necip; Kutlu, Selim; Akpolat, Nusret (Elsevier Science Inc, 2008)
OBJECTIVES To investigate the effects of terazosin and melatonin on isolated rabbit bladder strips after partial bladder outlet obstruction and determine responses to agonist-induced contractility and changes in oxidant-antioxidant system. METHODS We created partial bladder outlet obstruction in 5 groups of rabbits, each containing 8. Rabbits with sham operation (group 1) received no drug treatment. Similarly, animals in group 2 underwent partial bladder outlet obstruction and received no drug treatment. Rabbits in groups 3 were administered 5 mg/day oral terazosin, and rabbits in group 4 received 10 mg/kg/day melatonin intraperitoneally. Animals in group 5 received both terazosin and melatonin. We removed their bladders and performed histopathological and biochemical measurements. We assessed tissue malondialdehyde and antioxidant enzyme activity levels and recorded in vitro contractility response to KCl in isolated organ baths. RESULTS The thickness of muscularis propria was significantly increased in group 2 compared with all other groups. KCl-evoked contractions after partial outlet obstruction were significantly impaired in group 3 and 4 animals receiving terazosin and melatonin, respectively. However, combined use of melatonin and terazosin in group 5 showed contractility responses similar to sham-operated animals (P < 0.05). Melatonin administration to groups 4 and 5 showed decreased levels of lipid peroxidation. Similarly, animals receiving melatonin and melatonin plus terazosin showed statistically significant increase in antioxidant enzyme activities. CONCLUSIONS In the present study, we showed that oxidative stress induced by partial bladder outlet obstruction can be successfully antagonized by the potent antioxidant melatonin, and its combined use with an alpha-antagonist such as terazosin may restore in vitro contractility.
Keywords: Urinary-Bladder; Doxazosin; Ischemia/Reperfusion; Tadenan; Growth; Assay